Early Progesterone Change Associated With Pregnancy Outcome After Fresh Embryo Transfer in Assisted Reproduction Technology Cycles With Progesterone Level of >1.5 ng/ml on Human Chorionic Gonadotropin Trigger Day - Lee, Chun-I; Chen, Hsiu-Hui; Huang, Chun-Chia; Lin, Pin-Yao; Lee, Tsung-Hsien; Lee, Maw-Sheng (Frontiers in Endocrinology, 2020)
Several studies have reported a poor implantation rate for assisted reproduction technology (ART) cycles with elevated progesterone (P4) at the end of the follicular phase. Whether all women with increased P4 on the human chorionic gonadotropin(hCG) trigger day should undergo fresh or frozen embryo transfer (ET) remains to be explored. This study attempted to determine that the P4 level on 2 days before hCG administration and P4 ratio can serve as indicators for fresh ET in normal responders with an elevated P4 level of >1.5 ng/ml on the hCG administration day. This was a retrospective cohort study involving337 ART cycles with fresh ET for normal responders. Serum P4 levels were measured 2 days prior to hCG day (P4 level I) and on the hCG administration day (P4 level II). The P4 ratio was calculated as follows: P4 ratio= P4 level II / P4 level I. The primary outcome is live birth rate of fresh ET cycles. The ROC curves established that the optimal P4 level I and P4 ratio for pregnancy in ART cycles with high P4 level II were 0.975ng/ml and 1.62, respectively. Patients with a P4 level I of ≤0.975 ng/ml and P4 ratio of >1.62 were associated with a significantly higher implantation (30.8%, 61/198 vs. 10.3%, 19/184, p<0.001) and live birth rates (51.6%, 33/64 vs. 15.0%, 9/60, p<0.001) compared with those with aP4 level I of >0.975 ng/ml and P4 ratio of ≤1.62. A combination of P4 level I and P4 ratio cutoff values of 0.975 ng/ml and 1.62, respectively, had a positive predictive value (PPV) of 82.5% for pregnancy. In conclusion, fresh ET can be an option for women with an early P4 level I under 0.975 ng/ml and a P4 ratio higher than 1.62, especially for those normal responders with an elevated P4 level II >1.5 ng/ml on the hCG administration day. This approach may shorten the time to pregnancy and reduce the cost of ART cycles.